Estudo de flechas em vigas de concreto armado - Damasceno, Carlos Kalwendy Santos (Universidade Federal Rural do Semi-Árido, 2018)
Reinforced concrete structures are used in various engineering areas. Among these structures, the beams stand out. These are structural elements that can overcome large gaps and if correctly calculated and dimensioned can achieve a long lifetime. A very important aspect of this type of structure is the verification and determination of arrows. These allow the workpiece axis to move relative to the equilibrium position when the transverse loads act. Therefore, the theoretical and practical knowledge of this type of occurrence allows engineers to design safe and economical projects. In this way, this work has as general objective to carry out a theoretical survey in the classical literature and in scientific works on the behavior of arrows in beams. For that, extensive research was carried out in periodicals, standards and other related works. Other studies covering the same problem were analyzed, as well as other ways of calculating and sizing, as well as using alternative materials and components. Positive results were obtained for the reduction of the arrow, both in the presented methods and in the use of some alternative materials, in addition, the mixing of other components in the conventional concrete, improved the strength and stiffness of the beam, which resulted in smaller arrows.
Monografia
Keywords: Vigas; Flechas em vigas; Beams; Arrows on beams; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA